Cambrian small shelly fossils from the Çal Tepe Formation, Taurus Mountains, Turkey - Fernández-remolar, David; Göncüoglu, M. Cemal; Sarmiento, Graciela N. (Coloquios de Paleontología, 2001)
Lower and Middle Cambrian carbonate rocks of the Çal Tepe Formation, cropping out in the western Taurus Mountains, yielded a large number of microfossil remains. Small shelly fossils from a single level in the upper Lower Cambrian represent a high diversity biota that could be related to the «Cambrian explosion». Microfossil association from the lower Middle Cambrian sediments of the Çal Tepe Formation is taxonomically very reduced and a dominant taxon is Hadimopanella GEDIK. This sudden change could be attributed to a deepening of the basin during the early Middle Cambrian transgression.